Habitus Fotografer Wedding dan Prewedding di Kota Denpasar - Saputra, Gede Wahyu; Nugroho, Wahyu Budi; Mahadewi, Ni Made Anggita Sastri; Pramestisari, Nyoman Ayu Sukma (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2023)
Wedding and pre-wedding photography fall under the category of documentary photography. In Bali, these photography services are increasingly in demand, especially by the millennial generation in Denpasar City. Along with the increase in demand, the profession of wedding and pre-wedding photography has also increased. This research aims to examine the habitus that drives wedding and pre-wedding documentation photographers in Denpasar City to pursue the sector, and also how the habitus of these photographers later turns out to affect the personal style of the photos produced. This research uses Pierre Bourdieu's habitus concept as the basis for analyzing the problems that occur. The method used in analyzing the phenomenon of habitus of wedding and pre-wedding photographers in Denpasar City is descriptive-explanatory with a qualitative approach. From the research conducted, it was found that: 1) The habitus of wedding and pre-wedding photographers in Denpasar City is composed of the capitals they have and the realm where they practice. Capitals such as symbolic, cultural, economic, or social are found in different forms in each informant, and 2) Photographers' personal style is formed through their mindset, behavior, and preferences that are influenced by their social environment, culture, and past experiences. These habitual dispositions shape the way photographers act or respond in certain situations. Habitus can also influence the photographic techniques used in framing, composition and photo editing. Keywords: Wedding and pre-wedding photography, Photographer, Habitus, personal style.